2017
DOI: 10.1038/s41598-017-15805-8
|View full text |Cite
|
Sign up to set email alerts
|

Astrocyte elevated gene-1 promotes tumour growth and invasion by inducing EMT in oral squamous cell carcinoma

Abstract: Oral squamous cell carcinoma (OSCC) is a common human malignancy with a high incidence rate and poor prognosis. Although astrocyte elevated gene 1 (AEG-1) expression is up-regulated in various human cancers and plays an important role in carcinogenesis and tumour progression, the impact of AEG-1 on the development and progression of OSCC remains unclear. Accordingly, this study aims to clarify the biological significance of AEG-1 in OSCC. We found AEG-1 to be overexpressed in OSCC tissues compared to normal or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Among these candidates, MTDH was predicted as a major target of miR-655 ( Fig. 3A), which has been previously reported to be involved in OSCC occurrence and development (26)(27)(28)(29). To confirm this hypothesis, luciferase reporter assays were performed to determine whether the 3'-UTR of MTDH was directly targeted by miR-655 in OSCC cells.…”
Section: Mir-655 Directly Targets and Downregulates M Tdhmentioning
confidence: 73%
See 1 more Smart Citation
“…Among these candidates, MTDH was predicted as a major target of miR-655 ( Fig. 3A), which has been previously reported to be involved in OSCC occurrence and development (26)(27)(28)(29). To confirm this hypothesis, luciferase reporter assays were performed to determine whether the 3'-UTR of MTDH was directly targeted by miR-655 in OSCC cells.…”
Section: Mir-655 Directly Targets and Downregulates M Tdhmentioning
confidence: 73%
“…In addition, MTDH was previously confirmed as an independent prognostic factor for overall survival rates in OSCC patients (26,27). Highly expressed MTDH was reported to serve important roles in the onset and the progression of OSCC by affecting tumor cell growth, colony formation, migration and invasion (26,28,29). MTDH has previously been reported to be involved in the regulation of the PTEN/AKT signaling pathway (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…AEG-1 has emerged as an essential oncogene in regulating multiple aspects of cancer development and progression, including metastasis. It is important for tumor growth and cell migration and invasion mediated by EMT [19]. Increasing evidence shows that the level of AEG-1 is elevated in MM and that silencing of AEG-1 significantly inhibits the proliferation and metastasis of melanoma cells [20].…”
Section: Discussionmentioning
confidence: 99%
“…Only Ma et al have reported that MiR‐30e‐5p regulates the process of EMT in vitro; however, we also provide more pervasive in vivo evidence to strengthen the links between miR‐30e‐5p and EMT. In addition, mounting evidence has indicated that AEG‐1, as an oncogene, has an important function in the process of EMT and metastasis in diverse human solid cancers . miR‐30e‐5p and AEG‐1 can form an miR‐30e‐5p/AEG‐1 axis pathway, which regulates the metastasis and EMT of SCCHN.…”
Section: Discussionmentioning
confidence: 99%